Infiltration wells utilizing watershed conservation for flood prevention. Issue 1 (October 2021) - Situmorang, M; Setiyadi, S; Hutabarat, L E
Abstract: Rainfall is a determining factor in analyzing planned floods. This research was conducted by collecting secondary data and the field data concerning the soil's ability to infiltrate the volume of rainfall. Data processing is carried out by statistical analysis to estimate the average rainfall, intensity value, estimated discharge plan, volume of runoff and estimated infiltration rate. These parameters are important related to the infiltration well dimensions planning and the conserving water area. From the research results, it is shown that infiltration rate and optimal dimensions of infiltration wells very dependent on rainfall discharge and runoff volume in each region. Artificial infiltration is an alternative solution for maintaining groundwater balance and overcoming water problems. With groundwater infiltration, groundwater infiltration can maintain a relatively stable groundwater depth. Infiltration rate in RT 06 Cawang are 54, 03 cm/hour lower than in Kelurahan 11 Cawang East Jakarta are 54, 12 cm/hour, with perimeter area of wells DSP = 1, 5 m 2, Depth of well (HSP) = -1, 89 m 2 and coverage area of well (ASP) = 1, 77 m 2 .